Successful Strategies in Local Economic Development: An Examination of Global Practices and Their Implementation in Afghanistan - Fayaz Gul Mazloum Yar; Habib Ur Rahman Stanikzai (Eduvest - Journal of Universal Studies, 2024)
Local Economic Development (LED) is a pivotal strategy for fostering sustainable growth and alleviating poverty, particularly in fragile states like Afghanistan. This study examines successful global practices, such as South Korea's Saemaul Undong Movement, India's cluster development model, and Bangladesh's microfinance initiatives, to identify key success factors like governance, community participation, and infrastructure development. Using a mixed-methods approach, the research integrates qualitative insights from global case studies and Afghan stakeholders with quantitative data analysis. The findings highlight the need for decentralized governance, community-driven development, and financial inclusion to address Afghanistan's socio-economic challenges. Practical recommendations emphasize capacity building, infrastructure investments, and innovative financing mechanisms. This study contributes to bridging research gaps by contextualizing global strategies within Afghanistan’s unique socio-cultural and economic landscape, offering actionable insights for policymakers to achieve sustainable local economic growth.